Trajetórias de líderes do movimento social de catadores de materiais recicláveis : aspectos formadores de sua identidade - Souza, Juliana Soares de (2016)
This study investigated the causal relationship of the transformation of identity policymakers collectors for his role in the National Movement of Recyclable Materials, revealing his nature and assumptions, basing mainly on Social Psychology. By integrating the graduate program Science, Technology and Society, is marked throughout its development concern about the social relevance on the subject of dealings, as well as their contributions to the issue of deepening the scientific society, hoping to spark interest. To develop the work an analysis of the construction of identity from the life stories was carried out, considering the theoretical framework on identity, based on the work of the researcher Antonio Ciampa, "The story of Severino and the story of Severina - An essay on social psychology ". In this work, and a description about the recyclable material collector, from the autonomous and explored in the dumps and in the streets until organized in cooperatives, the literature review was treated social movements, their importance and classifications in contemporary times, in the Brazilian context and as a result, more specifically, the MCNR, through its history of struggle and achievements for the class of recyclable material collectors. As a result, we find that the identity of these individuals is marked by collective achievements that also revealing that humanity contained in these subjects could be held in self degree.